Ultimate performance : measuring human resources at work - Burkholder, Nicholas C. (John Wiley & Sons, 2007)
Meeting the challenges of high-performance HR. Until 1760 ships routinely disappeared, ran aground, or sank because seafarers could not measure longitude. The cost in life and property was immense. Today, business faces a similar challenge, as the failure to measure human resources performance is just as costly and deadly to modern organizations.